Immunomodulatory Effects Mediated by Serotonin - Rodrigo Arreola; Enrique Becerril-Villanueva; Carlos Cruz-Fuentes; Marco Antonio Velasco-Velázquez; María Eugenia Garcés-Alvarez; Gabriela Hurtado-Alvarado; Saray Quintero-Fabian; Lenin Pavón (Journal of Immunology Research)
Serotonin (5-HT) induces concentration-dependent metabolic effects in diverse cell types, including neurons, entherochromaffin cells, adipocytes, pancreatic beta-cells, fibroblasts, smooth muscle cells, epithelial cells, and leukocytes. Three classes of genes regulating 5-HT function are constitutively expressed or induced in these cells: (a) membrane proteins that regulate the response to 5-HT, such as SERT, 5HTR-GPCR, and the 5HT3-ion channels; (b) downstream signaling transduction proteins; and (c) enzymes controlling 5-HT metabolism, such as IDO and MAO, which can generate biologically active catabolites, including melatonin, kynurenines, and kynurenamines. This review covers the clinical and experimental mechanisms involved in 5-HT-induced immunomodulation. These mechanisms are cell-specific and depend on the expression of serotonergic components in immune cells. Consequently, 5-HT can modulate several immunological events, such as chemotaxis, leukocyte activation, proliferation, cytokine secretion, anergy, and apoptosis. The effects of 5-HT on immune cells may be relevant in the clinical outcome of pathologies with an inflammatory component. Major depression, fibromyalgia, Alzheimer disease, psoriasis, arthritis, allergies, and asthma are all associated with changes in the serotonergic system associated with leukocytes. Thus, pharmacological regulation of the serotonergic system may modulate immune function and provide therapeutic alternatives for these diseases.